Do Standardized Test Scores Influence Parental Choice of High School? - John Maddaus; Scott F. Marion (Journal of Research in Rural Education, 1995)
While the debate on school reform frequently has linked standardized testing and school choice, there is little empirical evidence that students or their parents use published test scores in choosing schools, especially in rural areas of the United States. Selected communities in Maine offer the opportunity to explore the relationship between testing and school choice because ofthe combination oftown-tuitioned high school students, local control ofschools, and published scores from the Maine Educational Assessment (MEA). On the basis of both bivariate and multivariate analyses, we conclude that published test scores influence school choice in rural Maine towns that tuition their students. However, our findings suggest that otherfactors also may influence school choice.